Association between Vitamin D Receptor Polymorphism and Serum Vitamin D Levels in Children with Low-Energy Fractures. (2nd January 2017) - Karpiński, Michal; Galicka, Anna; Milewski, Robert; Popko, Janusz; Badmaev, Vladimir; Stohs, Sidney J.
Abstract : Objective: Fractures of bones, especially forearm fractures, are very common in children and their number is increasing. This study was designed to determine the impact of vitamin D serum levels and vitamin D receptor (VDR) polymorphisms on the occurrence of low-energy fractures in children. Methods: The study group consisted of 100 children with clinically relevant bone fractures and a control group consisted of 127 children without fractures. Total vitamin D [25(OH)D3 plus 25(OH)D2] serum concentrations were evaluated in every patient. Genotypes for 4 restriction fragment length polymorphisms of the vitamin D receptor gene ( Fok I, Apa I, Taq I, and Bsm I) were determined by standard polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) techniques. Results: Differences in concentrations of vitamin D were observed between the group with bone fractures (median = 12 ng/ml) and the control group (median = 16 ng/ml; p = 0.000044). Higher levels of vitamin D reduced the risk of fracture by 1.06 times ( p = 0.0005). No impact of particular VDR polymorphism on the occurrence of low-energy fractures in children was detected. However, there were significant differences in the prevalence of Fok I polymorphism genotypes between the fracture and control groups ( p = 0.05). Furthermore, the recessive "aa" genotype of Apa I polymorphism and the dominant "TT" genotype of Taq I polymorphism were associated with higher levels of vitamin D ( p = 0.005 and p = 0.036, respectively). Conclusions: Vitamin D deficiency is an independent risk factor for fractures in children. Apa I polymorphism recessive "aa" and Taq I polymorphism dominant "TT" genotypes are associated with higher levels of vitamin D in serum.